Exploring Transformative Learning at the Cultural Interface: Insights From Successful Aboriginal University Students - Hill, Braden; Winmar, Grantley; Woods, Jenna (The Australian Journal of Indigenous Education, 2020)
Transformative learning theory articulates a process whereby students experience a change in perspectives that expands and transforms their worldview. Despite being well established and regarded within the literature relating to adult and continuing education, Mezirow's (1978) seminal education theory remains largely absent in the research relating to Indigenous higher education. This study explores the transformative impact of university learning on the student journeys of three Aboriginal graduates from a Western Australian university. Applying a collaborative auto-ethnographic approach, each author-participant's personal narrative of their student experience was exposed to comparative, thematic and critical analysis. It was found that each author had faced similar cognitive and emotional challenges at university. Significantly, it emerged that university had changed the author-participants’ identities in ways that aligned with Mezirow's transformative learning construct. The narrative data also revealed elements that appeared related to the students’ negotiation of Nakata's cultural interface. A dominant theme in the data referred to the relationships formed during university, as being integral to transformation. Furthermore, family was understood to have a paradoxical influence on their educational journey. The insights garnered from this study prompt further consideration as to how transformative learning theory might be mobilised at the cultural interface.